Bob books. Sight words first grade - Kertell, Lynn Maslen (Scholastic, 2010)
"Sight words are among the most frequently used words in the English language. Bob Books Sight Words First Grade introduces 30 sight words perfect for developing young readers. Consistent short vowels, simple stories, and word repetition ensure that each book gently advances your child's skills while building confidence. Inside you'll find: 10 easy-to-read, hilarious books ; 30 two-sided flash cards. 20 new sight words--3 introduced in each story. Context clues and illustrations give sight word hints. Consistent short vowels for each decoding in the rest of the story"--p. [4] of container.